Determining Fire Door Resistance Through Infrared Thermography - Mustafa ALTIN (International Journal of Applied Methods in Electronics and Computers, 2016)
The resistance tests of two fire doors with standard opening single were made using the methods of thermocouples and infrared thermography according to the features stated in the regulations. With the traditional fire mechanism stated in the regulation of TS EN 1634-1, a fire resistance test of 50 and 56 minutes was made. In the 32nd and 34th minutes of the experiment, opening was observed at the upper right-hand corners of standard opening single fire doors that were tested. Temperature values obtained from the measurement points stated in the regulation were controlled and with 200 thermal images that were obtained image process were applied. The utility of Infrared Thermography (IRT) method that is a contactless and distant measurement technique of temperature is shown to be used for fire tests with the traditional methods.